EVALUATION OF THE IMPLEMENTATION OF INTERNAL CONTROL IN SALES AND CASH RECEIPT ACCOUNTING SYSTEM (Case Study at PG Kebon Agung Malang) - Santa Berta Maharani (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
Sales activity is a part of accounting system that gives a big contribution to cash receipt. Sales transaction should be done by some related functions, they are sales function, cash function, warehouse function, shipping function, and accounting function. Those functions have to stand alone and there should be no overlapping. Cash receipt has an important role in a company since it is the lifeblood of the company. To support the sales and cash receipt procedure, it needed a well adequate internal control structure and required companies that are competent. The purpose of internal control is to reduce the occurrence of error, misuse and corruption as well as can be encouraging the effectiveness of sales and cash receipt procedure.In this research formulation the problem is implementation of sales and cash receipt accounting system, implementation of sales and cash receipt accounting system in supporting internal control, the obstacle and solution of sales and cash receipt procedure in PG Kebon Agung Malang. Type of research is qualitative research with descriptive approach. Focus in this research is organizational structure, procedure of sales and cash receipt , internal control over sales and cash receipt accounting system. The result of the research shows that the implementation of the sales and cash receipt accounting system in supporting internal control is good enough there is a clear separation of jobs of each department/function so there is no overlapping task. The weaknesess of this company is the absence of Shipping Department makes the buyer (auction winner) have to take their sugar by themselves to the Warehouse Department. For the future PG Kebon Agung needs an shipping department to deliver the sugar to the buyer (auction winner) to make them easier in bringing a big amount of sugar. Keywords: Sales, Cash Receipt, Internal Control